Perancangan Buku Cerita Bergambar sebagai Media Edukasi tentang Penyakit Cacingan bagi Anak - Jessica Crysta Varani; Yasermi Syahrul (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2025)
Worm infections remain a common health problem in Indonesia, especially in children, with a prevalence of 45–65%. The lack of appropriate educational media for children makes picture books a potential alternative visual communication medium for conveying health information. This study aims to design a picture book as an educational medium about worms for children aged 4–8 years. The method used refers to the design approach of Eric Karjaluoto, which includes the stages of discovery, planning, creativity, and application. Data were collected through field observations, interviews, documentation, and literature studies in the West Jakarta area. The design results in a book entitled